1951
DOI: 10.1590/s0006-87051951000200002
|View full text |Cite
|
Sign up to set email alerts
|

A água do solo e o sombreamento dos cafezais na américa central

Abstract: The coffee plant does not thrive well under shade in most of the coffee areas of the State of São Paulo, Brazil. It has been shown that water competition from the shade trees during the dry season is the factor responsible for the failure in growing coffee under shade in São Paulo. In all cases where the coffee plants were not thriving well under shade, the soil moisture after two to three months of drought was at the wilting point at the depths most utilised by the root systems of sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…If high agrochemical applications are feasible, for example when crop prices are high and environmental issues are not considered, maximum attainable yields per hectare are often higher without shade (Willey, 1975). In seasonally dry zones, root competition for water may limit the use of shade trees for coffee (Franco, 1951 ). Pest and disease problems may increase (Fonseca, 1939;Dakwa, 1980;Smith, 1981;Wrigley, 1988;I CAFE, 1989b) or decrease (Tapley, 1961;Ahenkorah et al, 1974;Nataraj and Subamanian, 1975;Smith, 1981;Eskes, 1982;Campbell, 1984) with increased shade.…”
Section: Source: Lock (1888)mentioning
confidence: 99%
See 1 more Smart Citation
“…If high agrochemical applications are feasible, for example when crop prices are high and environmental issues are not considered, maximum attainable yields per hectare are often higher without shade (Willey, 1975). In seasonally dry zones, root competition for water may limit the use of shade trees for coffee (Franco, 1951 ). Pest and disease problems may increase (Fonseca, 1939;Dakwa, 1980;Smith, 1981;Wrigley, 1988;I CAFE, 1989b) or decrease (Tapley, 1961;Ahenkorah et al, 1974;Nataraj and Subamanian, 1975;Smith, 1981;Eskes, 1982;Campbell, 1984) with increased shade.…”
Section: Source: Lock (1888)mentioning
confidence: 99%
“…The influence of shade trees on water availability for the understory crop in seasonally dry zones is as important a research topic now as when Franco (1951) identified it as the main justification for eliminating shade trees from coffee plantations in many areas of Brazil. Competition for water can occur, even in tropical rain forest areas, during short dry periods (Kozlowski, 1982).…”
Section: Competition Between Trees and Cropsmentioning
confidence: 99%
“…(1) Shade tree root competition for moisture during the dry season and oxygen during the wet season [3,34,36,47,57,90].…”
Section: Detrimental Influences On the Hydrological Cyclementioning
confidence: 99%
“…Several studies on the influence of rainfall frequency and irrigation on growth and production of coffee have been made, also measurements of plant transpiration have been reported at different natural conditions (DEAN 1939;NUT-MAN 1941;FRANCO 1951FRANCO , 1952FRANCO & INFORZATO 1950-1951. Generally speaking coffee plants seem to be rather resistant to drought although the growth may be depressed to a large extent (GUISCAFRE-ARRILAGA 1957;RINGOET 1952;SYLVAIN 1959).…”
Section: Introductionmentioning
confidence: 99%